Η αλληλογραφία του αγίου Κωνσταντίνου Καβάσιλα με τον αρχιεπίσκοπο Αχρίδος Δημήτριο Χωματιανό και τον επίσκοπο Κίτρους Ιωάννη - Nedeski, Viktor (Υπουργείο Πολιτισμού και Αθλητισμού, 2021)
Saint Constantine Cabasilas was an eminent archpriest of the Ohrid Archbishopric, but due to historical circumstances that followed shortly after his primacy, today we have partial and scarce data of his life and work. Along with the hymnological works of this church father, crucial for the clarification of his work are his correspondences with two eminent contemporaries: the Archbishop Demetrius Homatianos and John the Bishop of Kitrus. His correspondence with Homatianos dates to the period of Constantine’s episcopacy in Strumica. Correspondence with Homatianos, as well as with the Bishop John culminates in the period when saint Constantine Cabasilas was Metropolitan of Durres. This correspondence constitutes an important source, especially with reference to the church law as well as the liturgical and the current interdenominational dialogue. The precision of the asked questions and the subsequent answers, which were explicit down to minor details, resulted in a sophisticated elaboration on topics that are still current today. This also testifies to the great education of these clerics. However, the studious approach to current but also to more serious ecumenical prob lems discloses their dedicated service to God and to the entrusted people; the manner in which they use the principle of economy (οικονομία) and akrivia (ακρίβεια) is a good model for solving particular contemporary church issues.